PENGGUNAAN PENANDA BIOLOGIS ANGIOGENIK RASIO s-Flt1 DAN PIGF SEBAGAI PREDIKTOR PREEKLAMSIA - Levani, Yelvi (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Preeclampsia is a leading cause of maternal death worldwide. Preeclampsia involves multi-organ and characterized by hypertension and proteinuria. One of the hypothesis pathogenesisin preeclampsia is placental insufficiency. Its causing imbalance between angiogenic and antiangiogenic factors in maternal circulation. This imbalance factors are responsible for systemic vasoconstriction. However, until now, there is no predictor for preeclampsiain high risk pregnancy. Therefore, this review briefly describes the recent studies about utility of biologic angiogenesis marker, such as s-Flt1 and PIGF as predictor in preeclampsia